2019
DOI: 10.1021/acs.jpca.8b12508
|View full text |Cite
|
Sign up to set email alerts
|

π-Hydrogen Bonding Probes the Reactivity of Aromatic Compounds: Nitration of Substituted Benzenes

Abstract: The shifts of phenol O–H stretching vibration frequencies [Δν­(OH)exp] upon π-hydrogen bonding with aromatic compounds is proposed as a spectroscopic probe of the reactivity of aromatic substrates toward electrophiles. A single infrared spectrum reflecting the Δν­(OH)exp shift for an aromatic species in a reference solvent (CCl4 in this study) provides a good estimate of reactivity. The methodology is applied in rationalizing reactivity trends for the BF3 catalyzed nitration by methylnitrate in nitromethane of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Considering the nature of this initial step, we investigated the correlations between phenol Δν­(OH) exp shifts induced by π-hydrogen bonding with aromatic substrates. The experimentally recorded phenol Δν­(OH) exp shifts are juxtaposed to the relative rate constants (log k rel ) for the nitration of a series of aromatic derivatives (methylbenzenes, monoalkylbenzenes, halobenzenes, and anisole) by methyl nitrate in the presence of BF 3 in nitromethane solvent (literature kinetic data, see footnotes to Table in ref ). The reaction is illustrated in Scheme .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the nature of this initial step, we investigated the correlations between phenol Δν­(OH) exp shifts induced by π-hydrogen bonding with aromatic substrates. The experimentally recorded phenol Δν­(OH) exp shifts are juxtaposed to the relative rate constants (log k rel ) for the nitration of a series of aromatic derivatives (methylbenzenes, monoalkylbenzenes, halobenzenes, and anisole) by methyl nitrate in the presence of BF 3 in nitromethane solvent (literature kinetic data, see footnotes to Table in ref ). The reaction is illustrated in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“… a Relative rate with respect to benzene ( k benzene = 1). See ref and references therein for the sources of experimental kinetic data and Δν­(OH) exp shifts. b Theoretical computations for modeled nitromethane solvent. c The correlation coefficients (absolute values are shown) refer to the linear regressions between the experimental log k rel values and the predicted values according the 2nd order polynomial expressions. …”
Section: Resultsmentioning
confidence: 99%
“…In a previous research we have shown that the molecular electrostatic potential values, evaluated at some distance over the aromatic ring centroid, may provide a good description of the effect of aromatic substituents on the π‐hydrogen bonding and nucleophilic reactivity of the aromatic derivatives considered . We applied here a similar approach in the search for appropriate theoretical parameters to describe the nucleophilic reactivity of the alkenes.…”
Section: Resultsmentioning
confidence: 99%
“…Pursuant to computations of atomic charges, we also evaluated another theoretical quantity, recently introduced for studies of aromatic systems, the shifts of molecular electrostatic potential at a point in the molecular space in close proximity to the reaction center atoms . For the benzene derivatives studied we used the MESP shifts (relative to benzene) at 1.5 Å over the centroid of the aromatic ring [Δ V (1.5)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation